Exploring the Link Between Islamic Philanthropy (ZIS) and Happiness: A Panel Data Analysis in Indonesia - Berlyansyah, Seftyana Indica; Kafabih, An'im (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2025)
This study investigates the determinants of the Indonesian Happiness Index, specifically examining the impact of income and Islamic philanthropy (Zakat, Infaq, and Sedekah or ZIS). Utilizing panel data from 19 provinces for the years 2017 and 2021, the research employs a Random Effect Model (REM) to analyze the relationships between happiness and key socio-economic variables, including Gross Regional Domestic Product (GRDP), charitable giving, poverty, and health. The empirical findings reveal that charitable giving through ZIS has a positive and significant effect on happiness, suggesting that religiously motivated altruism is a key driver of well-being in Indonesia. In contrast, income demonstrates a significant negative relationship with happiness, aligning with the Easterlin Paradox which posits that economic growth does not necessarily lead to greater life satisfaction. Furthermore, health complaints significantly reduce happiness, whereas poverty levels show no statistically significant impact. These results imply that policymakers should prioritize strengthening philanthropic governance, as promoting ZIS offers a strategic pathway to enhance societal well-being beyond material economic measures